The Effect of Culture Tourism Development on Ethnic Minorities and Its Influence on the Visitor Experience: Case Study Lijiang, China - Yang, Xinghe (Auckland University of Technology, 2018)
Cultural heritage is an indispensable attraction for tourism. Heritage tourism can help to achieve poverty alleviation in some areas, but it can also lead to unsustainable situations and even longterm destruction of the cultural resource. The danger of the existence of a vicious development model is that the demand for tourism leads to commercialization, and tourist gentrification – specifically when related to heritage cities and villages. This can lead to a perceived lack of authenticity which will in turn reduce visitor satisfaction to some extent. As a result, continued unmanaged development may lead to alienation of local stakeholders and a diminished tourism experience. Discussions on heritage, its value, and local consequences requires a targeted approach. Balancing the economic benefits and maintaining the core value of cultural heritage is a particularly challenging task. Therefore, the main purpose of this paper is to understand the impact of tourism development on heritage cities with ethnic minorities, specifically focusing on the ancient city of Lijiang in China. The main research question was defined as: ”What are the effects of tourism development on local culture and the visitor experience within the old town of Lijiang, China.” Because of the increase in urbanization and tourism, excessive commercialization and gentrification have affected the sustainable resource management of heritage sites. Legacy is not a renewable resource; it should be effectively preserved. However, because of its management complexity, there is no unified method. This study uses a qualitative method of inductive inference. The research phase begins with a secondary data collection based on the research questions. Through identifying the stages of tourism development in Lijiang, introducing the government management structure , as well as the government’s management strategies at different times, conclusions could be made in terms of restrictions on remaining residents, and a general loss of local homeownership in favour of non-local entrepreneurship. As a second research method, visitor reviews of a travel website (Tripadvisor) were collected over 3 periods (2009-2011, 2012-2014, 2015-2017), and analysed via thematic coding. This allowed for a recognition of overall trends in changes to the visitor experience from 2009 to 2017, specifically: positive reviews (such as the perception of the attractiveness of the ancient city) have declined year by year, and negative reviews (such as lack of authenticity and over-development) have increased year by year. Therefore, the study found that the government’s management strategy mainly aimed at the uninterrupted growth of the tourism industry and tourism gentrification are two major factors that hinder the sustainable development of Lijiang heritage tourism. Therefore, this dissertation proposes to strengthen the understanding of the non-market value of the ancient city, changing the business philosophy, redefining the functional location of the ancient city and creating quality tourism products. Through this, tt may be possible to try to improve the status quo in Lijiang and realize the sustainable development of ancient city tourism. While the use of longitudinal analysis of visitor reviews offers an interesting monitoring tool, there were also some inherent limitations to the study design. The history of the Old Town's planning and management strategy could only be reviewed through secondary data. This may not be very comprehensive and detailed and cannot exactly match the timeframes for which tourism reviews were collected. At the same time, the factors of group thinking and social influence in the review cannot be ruled out. For future research it is suggested that a more in-depth interview approach can better understand the Naxi community's views on the current tourism development. As far as the second topic of this study is concerned, on the travel experience, more understanding can be provided by comparing the comments of domestic and foreign tourists and associating tourism experiences with tourism characteristics.
Keywords: Cultural heritage; Tourism management; Heritage tourism; Culture tourism; Ethnic minorities; Influence of urbanization; Lijiang